The Uses of X/Twitter by Members of the TESOL Community - Lee, Kent; Abbott, Marilyn L.; Wang, Shiran; Lang, Jacob (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2023)
A lack of dialogue and collaboration between researchers and practitioners has been recognized in the field of second language education. Social media platforms such as X/Twitter have potential for connecting professionals in the teaching of English to speakers of other languages (TESOL) community and supporting professional learning and research; however, studies of TESOL professionals’ uses of X/Twitter have only examined posts/tweets from a limited number of communities marked by hashtags/ keywords. This study identifies 23 hashtags relevant to TESOL instruction for adults in the Canadian context and used them as search parameters to extract a data set of 4,833 posts/tweets. Eighty-two North American university professors who had published in the field of TESOL, were selected and searched for on X/Twitter. Upon locating 15 X/Twitter professor accounts, all 272 posts/tweets posted over the one-year period, were extracted. Two content analyses were conducted to infer the purpose of the posts/ tweets and identify the hashtags used by the professors. Results reveal considerable variation in the professors’ and other TESOL community members’ uses of X/Twitter and suggest that the two groups participate in rather separate X/Twitter communities. Recommendations for maximizing X/Twitter as a tool for professional learning and research and fostering the research-practice link are provided.